Rethinking race : Franz Boas and his contemporaries - Williams, Vernon J. (University Press of Kentucky, 1996)
In this thought-provoking reexamination of the history of ""racial science"" Vernon J. Williams argues that all current theories of race and race relations can be understood as extensions of or reactions to the theories formulated during the first half of the twentieth century. Williams explores these theories in a carefully crafted analysis of Franz Boas and his influence upon his contemporaries, especially W.E.B. DuBois, Booker T. Washington, George W. Ellis.